2010
DOI: 10.1073/pnas.1015553107
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 knockout mice exhibit impaired induction of mGluR-dependent long-term depression at CA3-CA1 synapses

Abstract: Group I metabotropic glutamate receptors (mGluR1/5) are important to synaptic circuitry formation during development and to forms of activity-dependent synaptic plasticity. Dysregulation of mGluR1/5 signaling is implicated in some disorders of neurodevelopment, including fragile X syndrome, the most common inherited form of intellectual disabilities and leading cause of autism. Site(s) in the intracellular loops of mGluR1/5 directly bind caveolin-1, an adaptor protein that associates with membrane rafts. Caveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…These results extend those that have shown that the loss of Cav-1, either through siRNA or transgenic models, can blunt neuroprotection (9) and metabotropic glutamate receptor-mediated long-term depression (43,59) and accelerate a neurodegenerative phenotype (32,60,61). Our findings obtained with siRNA-mediated Cav-1 knockdown extend the role of Cav-1 in neuronal signaling to a variety of receptors in addition to glutamate.…”
Section: Syncav1supporting
confidence: 76%
See 2 more Smart Citations
“…These results extend those that have shown that the loss of Cav-1, either through siRNA or transgenic models, can blunt neuroprotection (9) and metabotropic glutamate receptor-mediated long-term depression (43,59) and accelerate a neurodegenerative phenotype (32,60,61). Our findings obtained with siRNA-mediated Cav-1 knockdown extend the role of Cav-1 in neuronal signaling to a variety of receptors in addition to glutamate.…”
Section: Syncav1supporting
confidence: 76%
“…Cav-1 and membrane/lipid rafts can regulate estrogen receptor signaling (58), glutamate receptor neurotransmission (9,43,59), and neurotrophin receptor signaling (TrkB and p75) (14,57). Although NMDAR subtypes are critical for neuroprotection against ischemic injury and for neurotransmission, their localization to extrasynaptic regions can facilitate neuronal cell death (33).…”
Section: Syncav1mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute hippocampal slices (400 μm) were prepared from age-matched WT and mutant mice by using conventional techniques (30). fEPSPs were evoked by square pulses (10-100 μA, 100 μs) with a concentric bipolar tungsten stimulating electrode.…”
Section: Methodsmentioning
confidence: 99%
“…We next examined mGluR-LTD at DGC synapses of Pten cKO mice. mGluR-LTD is an NMDA receptor (NMDAR)-independent, protein synthesis-dependent (28) form of homosynaptic LTD and can be elicited by application of the group mGluR agonist (R,S)-3,5-dihydroxyphenylglycine (DHPG) at CA1 (29,30) and DGC synapses (31). mGluR-LTD was significantly impaired in young, middle-aged, and old Pten cKO relative to that of age-matched WT mice (Fig.…”
Section: Dysregulation Of Tbs-ltp At Dgc Synapses Of Pten Cko Mice Ismentioning
confidence: 99%